2004
DOI: 10.1258/0022215041615155
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandins, leukotrienes and perennial rhinitis

Abstract: Prostaglandins and leukotrienes are implicated in conditions of both the upper and lower airways. In the former they are deranged in nasal polyposis, intrinsic rhinitis and allergic rhinitis while in the latter they are involved in the pathogenesis of asthma. The aim of the present study was to measure mucosal eicosanoid levels in the three types of rhinitis and compare with controls. In addition, the effect of topical steroids on eicosanoid levels in rhinitis was examined. The levels of prostaglandins E(2) (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…PGD2 provokes a dose‐dependent increase in congestion in patients with and without AR [25, 42]. However, PGF2α increases the nasal patency [25] and PGE2 is a constrictor of nasal vasculature, leading to decongestion [59]. Thus, prostanoids exhibit a complex interplay of effects, and nasal vasoconstriction is most probably the overriding effect in vivo .…”
Section: Mast Cell‐derived Mediators Contribute To Nasal Obstructionmentioning
confidence: 99%
See 1 more Smart Citation
“…PGD2 provokes a dose‐dependent increase in congestion in patients with and without AR [25, 42]. However, PGF2α increases the nasal patency [25] and PGE2 is a constrictor of nasal vasculature, leading to decongestion [59]. Thus, prostanoids exhibit a complex interplay of effects, and nasal vasoconstriction is most probably the overriding effect in vivo .…”
Section: Mast Cell‐derived Mediators Contribute To Nasal Obstructionmentioning
confidence: 99%
“…Thus, prostanoids exhibit a complex interplay of effects, and nasal vasoconstriction is most probably the overriding effect in vivo . They may play a role in maintaining normal nasal patency [59].…”
Section: Mast Cell‐derived Mediators Contribute To Nasal Obstructionmentioning
confidence: 99%
“…prostaglandins and leukotrienes), which mediate several important physiological and pathological functions, and are also involved in the pathogenesis of many inflammatory airway diseases, including asthma, allergic rhinitis, chronic hyperplastic rhinosinusitis and nasal polyposis [20] . Evidence has shown that COX inhibition is due to inhibition of an antiallergic prostaglandin, most likely PGE 2 , which has been shown to downregulate inflammation by inhibiting the expression of both inflammatory mediators and their receptors [16] .…”
Section: Discussionmentioning
confidence: 99%
“…Other research has contradicted this with findings of significantly lower levels of PGE 2 , PGD 2 and LTE 4 in untreated rhinitics compared with controls [110], although there were no changes detected in levels of LTB 4 . Furthermore, this study reported that steroid treatment in these subjects apparently raised the levels of these eicosanoids apart from LTB 4 which was unaffected by the therapy [110]. These findings appear to refute the current thinking that increased levels of eicosanoids are implicated in the pathogenesis of IR.…”
mentioning
confidence: 98%
“…One study has reported increased levels of LTC 4 and PGD 2 in nasal lavage in symptomatic IR patients, compared with control subjects [109]. Other research has contradicted this with findings of significantly lower levels of PGE 2 , PGD 2 and LTE 4 in untreated rhinitics compared with controls [110], although there were no changes detected in levels of LTB 4 . Furthermore, this study reported that steroid treatment in these subjects apparently raised the levels of these eicosanoids apart from LTB 4 which was unaffected by the therapy [110].…”
mentioning
confidence: 99%